2018
DOI: 10.1177/0954407018804120
|View full text |Cite
|
Sign up to set email alerts
|

Gearshift control strategies for hybrid electric vehicles: A comparison of powertrains equipped with automated manual transmissions and dual-clutch transmissions

Abstract: This article describes gearshift control strategies developed for a series-parallel hybrid electric vehicle architecture in which an electric machine is connected to the output of the transmission, thus obtaining torque filling capabilities during gearshifts. Two transmission systems are analyzed: hybrid automated manual transmission and hybrid dual-clutch transmission. The article focuses on the gearshift control strategies for the two transmission, splitting each gearshift into several phases. The objectives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Scholar Guercioni G. R. analyzed the transmission system of a series-parallel hybrid electric vehicle architecture and conducted stage analysis and equation design for its shift control strategy. The results indicated that the controller exhibited good application performance in nonlinear dynamic models [11]. Scholar Jiang S. conducted theoretical derivations and modal energy analysis on the multi-stage gear transmission system of permanent magnet synchronous motors, considering electromagnetic effects and torsional resonance characteristics.…”
Section: Related Workmentioning
confidence: 99%
“…Scholar Guercioni G. R. analyzed the transmission system of a series-parallel hybrid electric vehicle architecture and conducted stage analysis and equation design for its shift control strategy. The results indicated that the controller exhibited good application performance in nonlinear dynamic models [11]. Scholar Jiang S. conducted theoretical derivations and modal energy analysis on the multi-stage gear transmission system of permanent magnet synchronous motors, considering electromagnetic effects and torsional resonance characteristics.…”
Section: Related Workmentioning
confidence: 99%
“…One of the important directions in the field of modernization and improvement of power transmissions is the use of design parameters to stabilize the operating modes of tractors [9]- [11]. In most cases, this results in an improvement of the interaction of the working parts of the machine with the processed environment and it is the main way of stabilizing the loading conditions of the tractor.…”
Section: B Research On the Stabilization Of Power Transmission Operating Modesmentioning
confidence: 99%
“…There has been developed a simulation model of the all-synchromesh gearbox, which differs from other models by its simplicity and quality, which can be calculated in real-time [18]. There is a large number of analyzes of different types of gearboxes, such as the control analysis of a hybrid automatic and manual gearbox and a hybrid double-clutch gearbox [9]. Also, the dynamic analysis of a vehicle with three different transmission configurations is of great interest [19], namely those with a spring-damper; a machine with a spring-damper combined with stabilizer bars; a machine with a spring-damper in combination with the hydraulically coupled roll-plane suspension.…”
Section: Research On the Improvement Of Mobile Machines Performancementioning
confidence: 99%
“…The reducer is an important component of the hybrid electric vehicle drive train. Compared to traditional fuel vehicles, its fatigue life depends not only on load conditions but also on the driving conditions, output characteristics of various power sources, etc [3][4][5][6]. Due to the shortcomings of the traditional reducer fatigue life test method, such as a long cycle and high cost, bench test by compiling load spectrum has become the main method of reducer fatigue testing in enterprises [7].…”
Section: Introductionmentioning
confidence: 99%